2020
DOI: 10.1186/s43058-020-00037-1
|View full text |Cite
|
Sign up to set email alerts
|

Reducing work pressure and IT problems and facilitating IT integration and audit & feedback help adherence to perioperative safety guidelines: a survey among 95 perioperative professionals

Abstract: Background To improve perioperative patient safety, guidelines for the preoperative, peroperative, and postoperative phase were introduced in the Netherlands between 2010 and 2013. To help the implementation of these guidelines, we aimed to get a better understanding of the barriers and drivers of perioperative guideline adherence and to explore what can be learned for future implementation projects in complex organizations. Methods We developed a questionnaire survey b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The IMPROVE-implementation programme involves a multifaceted intervention within the perioperative setting, tailored to: local barriers identified prospectively in the participating hospitals [ 15 ]; current performance and guideline adherence in the hospitals; and local needs and initiatives already realized or planned in the hospital. It uses evidence from scientific literature (systematic review of interventions by Grimshaw et al [ 8 ]); expert opinion (perioperative healthcare professionals as well as implementation experts [ N = 13 and 11 experts respectively, there was no overlap between groups] were asked to rate potential interventions in terms of their usefulness in improving perioperative guideline adherence) and knowledge and experience of the research team regarding the feasibility of the interventions (estimated costs, effort, and time for the hospitals as well as the research team) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IMPROVE-implementation programme involves a multifaceted intervention within the perioperative setting, tailored to: local barriers identified prospectively in the participating hospitals [ 15 ]; current performance and guideline adherence in the hospitals; and local needs and initiatives already realized or planned in the hospital. It uses evidence from scientific literature (systematic review of interventions by Grimshaw et al [ 8 ]); expert opinion (perioperative healthcare professionals as well as implementation experts [ N = 13 and 11 experts respectively, there was no overlap between groups] were asked to rate potential interventions in terms of their usefulness in improving perioperative guideline adherence) and knowledge and experience of the research team regarding the feasibility of the interventions (estimated costs, effort, and time for the hospitals as well as the research team) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…This framework is based on three models related to implementing change: the implementation of change-model of Grol and Wensing [ 25 , 26 ]; the framework of knowledge–attitude–behaviour-related barriers for guideline adherence of Cabana et al [ 27 ]; and the framework for adherence to clinical practice guidelines in the intensive care unit of Cahill et al [ 28 ]. We used the framework of Van Sluisveld et al also for our barrier analysis, prior to the actual implementation of the perioperative guidelines [ 15 ]. The categories of the framework van Van Sluisveld et al [ 24 ] relate to: 1. intervention characteristics (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adoption of clinical guidelines consists of 2 categories: primary strategies involving creation, mailing and publication, and secondary interventional strategies to reinforce the guidelines [18]. Emond et al [19] (2020) have found that obstacles for implementation of patient safety guidelines in the perioperative setting in the Netherlands were: time barrier (16% of the total number of barriers), emergency patients (8%), inefficient Information Technology (IT) structure (4%) and workload (3%). Van Gulik et al [20] have found that adherence is especially poor in terms of nonscheduled, flowchart-guided interventions.…”
Section: Ta B L E 3 Profile Of Systemic Analgesia Inmentioning
confidence: 99%
“…A qualitative study of multidisciplinary participants utilizing the Theoretical Domains Framework (TDF) by Munday et al (2019) identified a lack of knowledge around guidelines as well as social and environmental barriers. A Dutch survey focused on perioperative safety guidelines reported social and organizational barriers; perceptions that adherence to guidelines delay workflow and impacts routines, and that staff also did not always follow guidelines during emergency cases and believed patients would not expect them to as common barriers (Emond et al, 2020). Potential facilitators to improve uptake of guidelines included integrated information systems with audit and feedback; education; digital checklists as well as availability of warming and monitoring devices (Emond et al, 2020;Munday et al, 2019).…”
Section: Introductionmentioning
confidence: 99%